1993
DOI: 10.1149/1.2221657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12 Crown 4 on the Electrochemical Intercalation of Lithium into Graphite

Abstract: The cathodic decomposition of 1M LiCIO4 PC/EC electrolyte in presence of various amounts of 12 crown 4 during the first lithiation of graphite is investigated galvanostatically. The decomposition reaction is greatly reduced after addition of 12 crown 4 and reaches a limit at an optimum 12 crown 4 concentration of -0.35M. The reduction of electrolyte deeomposition after addition of 12 crown 4 is attributed to a significant decrease in gas evolution and possibly to the formation of a more stable SEI film.In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…378 The authors suggested that, unlike most of the additives that obey the empirical rule of the LUMO energy level, a crown ether might not be chemically involved in the formation of the SEI but rather affect this process indirectly by means of preferential solvation of lithium ions. Thus, the exclusion of PC molecules from the solvation sheath rather than the reductive decomposition of crown ethers is responsible for the reduced irreversible process at 0.80 V. 398 Their hypothesis was confirmed by the work of Aurbach and co-workers, who performed detailed FT-IR investigations on the graphitic anode surface that was cycled in electrolytes containing 12-crown-4. 250 Since the peaks corresponding to the possible reduction products of 12-crown-4 were absent in the spectra, they concluded that the effect of crown ether was not due to its participation in the buildup of the SEI.…”
Section: Anode: Sei Modificationmentioning
confidence: 88%
“…378 The authors suggested that, unlike most of the additives that obey the empirical rule of the LUMO energy level, a crown ether might not be chemically involved in the formation of the SEI but rather affect this process indirectly by means of preferential solvation of lithium ions. Thus, the exclusion of PC molecules from the solvation sheath rather than the reductive decomposition of crown ethers is responsible for the reduced irreversible process at 0.80 V. 398 Their hypothesis was confirmed by the work of Aurbach and co-workers, who performed detailed FT-IR investigations on the graphitic anode surface that was cycled in electrolytes containing 12-crown-4. 250 Since the peaks corresponding to the possible reduction products of 12-crown-4 were absent in the spectra, they concluded that the effect of crown ether was not due to its participation in the buildup of the SEI.…”
Section: Anode: Sei Modificationmentioning
confidence: 88%
“…Graphite materials have been extensively studied for use as negative electrodes in secondary lithium batteries. At the graphite electrode, lithium ions are intercalated into graphite upon charging and deintercalated upon discharging. The phase transition mechanism upon electrochemical Li intercalation has been investigated using X-ray diffraction 6-9 and Raman spectroscopy …”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolytes containing crown ethers are usually employed in secondary lithium batteries. In general, the addition of crown ethers has been demonstrated to improve the ionic conductivity at low concentrations affecting the rate of the Li electrode reaction [24][25][26] Shi et al employed an electrolyte containing the ionic liquid 1,2-dimethyl-3-propylimidazolium iodide and 18-crown-6 ether in DSSC. The devices containing crown-ethers exhibited a small enhancement in the short-circuit photocurrent.…”
mentioning
confidence: 99%